Experimental Method to Measure Anisotropic Transport in 2D Superconductors - Shalóm, D. E.; Pastoriza, H. (Springer Nature, 2004)
Fil: Shalóm, D. E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina